Cytotoxic effects of alkaloids on cervical carcinoma cell lines: a review - Priscilla Alencar Fernandes; Davi Antas e Silva; Micheline Azevedo Lima (São Paulo State University (UNESP), 2015)
Cervical cancer is the fourth type of women neoplasia, with thousands of new cases annually. It is closely related to human papillomavirus (HPV) infection, which has more than 13 oncogenic types, among them HPV 16 and 18 are implicated in 70% of cervical carcinoma cases. Alkaloids are nitrogenated and naturally occurring compounds, showing several uses in medical treatment, including cytotoxic and antineoplastic activities. In this work we aim to evaluate the cytotoxic and chemotherapeutic potential of alkaloids against cervical cancer. In order to accomplish this purpose, we have made a survey of potentially effective alkaloids with cytotoxic activities over HPV-16+ and HPV-18+ cells (HeLa cells). Through a literature review between the years of 1980 and 2015, we described the major alkaloid sources, distribution in nature and also discussed the mechanisms of action for their cytotoxicity. We found that alkaloids showed efficacy as cytotoxic agents, inhibiting cell growth of the HPV-transformed cells in vitro and in vivo by means of activation of intrinsic and extrinsic pathways of apoptosis, which included the clivage of caspases and PARP-1 (Poli-AdenosylRibose Protease 1), increase in p53 expression, release of cytochrome C and increase of cell death receptors expression like Fas, mainly observed in HeLa (HPV- 18+) cell lines. Moreover, these secondary metabolites helped in modulating the MDR (Multi-Drug Resistance) against the cell lines studied, which lead us to suggest their possible use as chemotherapeutic agents on the lesions caused by these viruses